2022
DOI: 10.1111/liv.15455
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationships between metabolic‐associated fatty liver disease and iron status: Two‐sample Mendelian randomization

Abstract: Background & Aims Dysregulated iron homeostasis plays an important role in the hepatic manifestation of metabolic‐associated fatty liver disease (MAFLD). We investigated the causal effects of five iron metabolism markers, regular iron supplementation and MAFLD risk. Methods Genetic summary statistics were obtained from open genome‐wide association study databases. Two‐sample bidirectional Mendelian randomization analysis was performed to estimate the causal effect between iron status and MAFLD, including Mende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…By means of Mendelian randomization as a robust epidemiological approach to analyse the causal estimation of fatty liver disease associated with metabolic dysfunction (also known as metabolic dysfunctionassociated fatty liver disease (MAFLD)) as an outcome using genetic variants, a study published in 2022 that included European individuals showed that the genetically predicted increase in liver levels of iron was associated with an increased risk of fatty liver disease. Although they need confirmation, these data support a causal association between deposition levels of iron in the liver and metabolic dysfunction 38 .…”
Section: Acquiredmentioning
confidence: 75%
“…By means of Mendelian randomization as a robust epidemiological approach to analyse the causal estimation of fatty liver disease associated with metabolic dysfunction (also known as metabolic dysfunctionassociated fatty liver disease (MAFLD)) as an outcome using genetic variants, a study published in 2022 that included European individuals showed that the genetically predicted increase in liver levels of iron was associated with an increased risk of fatty liver disease. Although they need confirmation, these data support a causal association between deposition levels of iron in the liver and metabolic dysfunction 38 .…”
Section: Acquiredmentioning
confidence: 75%
“…10 A recent Mendelian randomization study using data from the UK Biobank showed tentative evidence for a potential causal association of liver iron on fatty liver. 11 At the same time, oxidative stress induced by iron overload leads to increased insulin resistance, establishing a link between circulating markers of iron metabolism and T2D. 12 Sex-specific associations, with higher T2D risk conferred by elevated ferritin levels in women compared to men, have been reported.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…An association between markers of iron metabolism and liver disease has already been established 10 . A recent Mendelian randomization study using data from the UK Biobank showed tentative evidence for a potential causal association of liver iron on fatty liver 11 …”
Section: Introductionmentioning
confidence: 98%
“…Similar findings have been reported regarding the dietary intake of vitamin K ( 10 ). On the other hand, a mendelian randomization study showed an elevated risk of MAFLD associated with an increase in liver iron concentration ( 11 ). Multiple factors, such as oxidative stress-induced lipotoxicity and cellular senescence, contribute to the pathogenesis and progression of MAFLD ( 12 ).…”
Section: Introductionmentioning
confidence: 99%